Submitting a paper to an academic peer-reviewed journal, where to start? - van Teijlingen, E; Simkhada, PP; Rizyal, A (Health Renaissance, 2012)
DOI: http://dx.doi.org/10.3126/hren.v10i1.5997 HREN 2012; 10(1): 1-4